(3GdYed HGdCSWQdGH GdeSQWfs
(3ChdgG (B:s
(3GdMeO ddg Ydi eG hgH ef YhGQa cQeg hHYO aGdYed HGdCdGJ HGdbhd GdhGVM hCfG CbOe GdYed HGdCSWQdGH GdeSQWf s
(3BNQgG (B:s
(3heYQaI GdSGYGJ ceG LQJ GdYGOI ai CNPgG GdfXjQ ai GdCSWQdGH GdeWdb aCeG HbjI GdCYeGd ai gPG GdfhY aceG JbOe Ef TGA Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs